Exploring the relationship between sustainable entrepreneurship and the United Nations sustainable development goals: A comprehensive literature review - Shabbir, Muhammad Salman (Sustainable development (Bradford, West Yorkshire, England), 2023)
This research study aims to investigate the relationship between entrepreneurship and sustainable development, as well as explore how entrepreneurship can contribute to addressing the challenges associated with sustainable development. The significance of this topic lies in the fact that sustainable development is crucial for the long‐term well‐being of societies and the planet, and entrepreneurship has the potential to play a vital role in achieving sustainable development goals. Through a systematic literature review, this study evaluates how sustainable business activities can help achieve Sustainable Development Goal 8 (SDG 8‐Decent Work and Economic Growth). The study employs the Scopus indexing online database and VOSviewer, a data mining tool, to identify scholarly literature related to sustainable entrepreneurship and SDG‐8 published between 2015 and 2022. The bibliometric study indicates a significant growth in the scientific literature on this topic in recent years. The study identifies five research subjects, including current trends in the literature on SDGs, economic development, socioeconomic growth, durability, higher education, and other related topics. By conducting a thorough inquiry into the literature, this study aims to contribute to the understanding of the relationship between entrepreneurship and sustainable development, and provide insights into how entrepreneurship can be leveraged to achieve sustainable development goals. Ultimately, this research has important implications for policymakers, businesses, and individuals interested in promoting sustainable development and creating a more equitable and prosperous world.